การจัดการสวนปาล์มน้ำมันของสมาชิกสหกรณ์ปาล์มน้ำมันล้านนา จำกัด จังหวัดเชียงราย - ศิริชัย ฉายบัณฑิต (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The independent study purposed to study on the management of oil palm management by the members of Lanna Oil Palm Cooperative Limited in Chiang Rai Province. The study method consisted of information collection by in-depth interview and secondary data. The study populations were members of Lanna Oil Palm Cooperative Limited in Chiang Rai, using purposive sampling method to select the members who are knowledgeable, proficient and experienced in oil palm management not less than 5 years and own oil palm not less than 6 years. Their oil palm has suitable plantation managements according to the academic theory of Department of Agriculture, which means there are operating data record, regular revenue and expense statement of oil palm and having agricultural products at 2.3 – 3 tons/rai/year in average. There were 4 members in the top rank. In the study, their names would be replaced by A B C D instead of their real names for confidential purpose. According to the study, it was found that the 4 members have managed their oil palm plantation accurately by applying several theories. These theories composed of place selection, palm plant selection, gardening and harvesting. These members have been able to manage their oil palm to return a large amount of products every year, sorting members in order of their agricultural products from the top to the least; Member B, Member D, Member A and Member C respectively. After the analysis of capital cost, it showed that each member has different cost, sorting members in order of their cost in every year from the least to the highest; Member D, Member C, Member A and Member B respectively. The return analysis of members revealed the different result, sorting members of their return benefit in every year from the highest to the fewest; Member B, Member D, Member A and Member C respectively. Finally, regarding the analysis of payback period, the payback period of each member showed as the following: 9 years 7 months and 3 days of Member D, 12 years, 1 month and 8 days of Member A, 12 years, 5 months and 5 days of Member B and 18 years, 8 months and 1 day of Member C respectively. According to the result, the management of the members of Lanna Oil Palm Cooperative Limited in Chiang Rai is different in some factors which results to the different products. The member who has the most products prefers loam, using water from irrigation, digging 50x50 cm of hole size, bedding the hole with chemical fertilizers formula 0-3-0 with 300 g/plant, reviving the dead palm by a 9-month-old seedling, eradicating weeds 12 times a year, the following quantities of fertilizers in every year; 39.6 kg in year 1, 118.8 kg in year 2, 158.4 kg in year 3, 266.2 kg in year 4 and 297.0 kg in year 5, and lastly watering palms at 250 liters/plant/time. This differs from the member who has the fewest products regarding clay selection, using water from community’s water resource, digging 40x40 cm of hole size, bedding the hole by chemical formula 0-3-0 with 250 g/plant, reviving the dead palm by an 11-year-old seedling, eradicating weeds 18 times a year, the amount of fertilizers: 28.6 kg in year 107.8 kg in year 2, 151.8 kg in year 3, 239.8 kg in year 4 and 275.9 kg in year 5, and the watering palms for 180 liters/plant/time.